History teaching, cultural identities and Ibero-American consciousness in Spanish primary education textbooks - Ortega Sánchez, Delfín; Rodríguez Lestegás, Francisco (Historia y Memoria de la Educación, 2017)
This article analyzes the curricular treatment of Ibero-American history and the construction of an Ibero-American consciousness in Spanish primary education social studies textbooks. From inclusive and intercultural perspectives, the study approaches the mechanisms of consolidation and strengthening of the Cultural Ibero-American Space in the educational realm. It examines the historical and iconographic school narratives by means of the design, validation and application of five instruments for the data collection, analysis and evaluation, integrated into five categories of analysis: I. Identification and iconographic classification, II. Ordering and iconographic function, III. Historical narrative and cultural identity, IV. Activities and cultural identity, V. Validation. The results confirm the solid adoption of Eurocentric and hegemonic perspectives resulting from the absence of any real capacity for integrating social, cultural and historical contents or working towards to the consolidation of a Cultural Ibero-American Space or the construction of an Ibero-American cultural identity. The results report of the solid adoption of eurocentral and hegemonic perspectives opposite to the eloquent absence of a real of integration capacity of social, cultural and historical contents orientated to the consolidation of the Cultural Ibero-American Space and the construction of the recognized Ibero-American cultural identity